2013
DOI: 10.1016/j.phymed.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential anticancer compounds from Oplopanax horridus

Abstract: Oplopanax horridus is a plant native to North America. Previous reports have demonstrated that this herb has antiproliferative effects on cancer cells but study mostly focused on its extract or fractions. Because there has been limited phytochemical study on this herb, its bioactive compounds are largely unknown. We recently isolated and identified 13 compounds, including six polyynes, three sesquiterpenes, two triterpenoids, and two phenolic acids, of which five are novel compounds. In this study, we systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…The polyynes isolated from O. horridus have been evaluated for antiproliferative effects on some selected cancer cell lines such as human breast cancer cell line MCF-7, non-small cell lung cancer (NSCLC) cells, human colorectal cancer cell lines HCT-116 and SW-480 [21][22][23]. As shown in Table 1, the 22 polyynes exhibited different antiproliferative effects on the human breast cancer MCF-7, human lung adenocarcinoma epithelial A549, liver hepatocellular HepG2 and human breast cancer µM-231 cell lines.…”
Section: Effects Of the 22 Polyynes On Proliferation Of Selected Cancmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyynes isolated from O. horridus have been evaluated for antiproliferative effects on some selected cancer cell lines such as human breast cancer cell line MCF-7, non-small cell lung cancer (NSCLC) cells, human colorectal cancer cell lines HCT-116 and SW-480 [21][22][23]. As shown in Table 1, the 22 polyynes exhibited different antiproliferative effects on the human breast cancer MCF-7, human lung adenocarcinoma epithelial A549, liver hepatocellular HepG2 and human breast cancer µM-231 cell lines.…”
Section: Effects Of the 22 Polyynes On Proliferation Of Selected Cancmentioning
confidence: 99%
“…It was found that the compounds with higher anti-proliferative activity presented more potential cytotoxic effect on normal human hepatic cells as well (Table 1), which means these compounds may have potential hepatotoxicity in vivo. Actually, the safety and efficiency of O. horridus have not been evaluated totally thus far though it has a long history of use medicinally and as a dietary supplement [21,24], so more studies are definitely needed. …”
Section: Anti-proliferative Activity and Possible Structure-activity mentioning
confidence: 99%
“…The incidence of cancer is increasing with aging populations, and cancer is now the second leading cause of death in economically developed countries (World Cancer Report, 2014). Although effective for some cancers, current treatments, such as chemotherapy and radiation therapy, have a number of serious drawbacks, including challenging side effects, low selectivity, and problems with resistance (Gajendra et al, 2015;Wang et al, 2013). There is thus a need to continuously explore new cancer treatments that would hopefully overcome the drawbacks of existing therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the regulation of apoptosis may result in many pathological conditions and/or diseases such as cancer, autoimmune disorders, neurodegenerative diseases etc. (Kroemer and Reed 2000;Wang et al 2012Wang et al , 2013Ramasamy et al 2013). Once the cell looses control over apoptotic mechanism, cell evades death and divides continuously leading to neoplastic transformation (Igney and Krammer 2002;Hu and Kavanagh 2003;Reed 2003;Qi et al 2010).…”
Section: Introductionmentioning
confidence: 99%